DRUKI XV- WIECZNE W ZBIORACH BIBLIOTEKI KLASZTORU KARMELITÓW W CZERNEJ - Graczyk, Waldemar (Saeculum Christianum. Pismo Historyczne, 2017)
The monastery dedicated to St Elijah in Czerna was founded by Agnes of Teczynska Firlej in 1631. From its beginning the monastery collected works both for the celebration of liturgy and so as to deepen the knowledge and spirituality in the areas of asceticism, preaching and theology. Books usually came from donations and legacies. Currently in the resource library of old prints in Czerna there are 14 incunabula. Incunabula are not uniform provenance band books. They come from the ecclesiastical institutions, from individual person and from the clergy. Some of incunabula have an original binding, other have been replaced or refurbished. Though it is a small collection of books, in terms of quality it reflects the interests and needs of the environment. The smudged corners of the pages and the highlights made of part of the text can testify that these books were used by monks in deepening their knowledge.